Pengaruh Konsep Diri dan Kebiasaan Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP YP PGRI 4 MAKASSAR - Andi Patimbangi; Finsensius Hendi (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This research aims to: (1) understand the self-concept of students, habit of students, and students mathematics learning outcomes, (2) determine how the effects of self-concept on students mathematics learning outcomes, the influence of learning habit on students' mathematics learning outcomes, the influence of self-concept and learning habit with the students' mathematics learning outcomes.This research wasex-post facto research. The research was conducted in SMP YP PGRI 4 Makassar with sample 40 people. Data collection in this research used question naires and do cumentation. Technique of data analysis used simple linear regression and multiple regressions. The results showed that (1) the concept of self concept of the students, learning habit, and learning outcomes have a tendency in the high category, (2) a significant difference between self concept and mathematics learning outcomes, learning habit with students' mathematics learning outcomes, self concept and learning habit with the learning outcomes of VIII grademath students of SMP YP PGRI 4 Makassar.